2017
DOI: 10.1007/s00383-017-4149-5
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent and metastatic congenital mesoblastic nephroma: where does the evidence stand?

Abstract: Recurrence and metastasis in cellular CMN are much more common than described earlier and carry a high mortality. Children with cellular and mixed CMN require close clinical and radiological follow-up for a minimum of 12 months after primary surgery. Surgery is the mainstay of the treatment of recurrent and metastatic lesions. Neoadjuvant chemotherapy is recommended only if the lesion is inoperable. Targeted therapy may be an option in treatment of refractory cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 35 publications
0
30
0
6
Order By: Relevance
“…As suggested by the aggressive pathological features, the cellular variant is more aggressive with local recurrence, and distant metastases 17 . Since recurrence and metastasis in cellular CMN are much more common and carry a high mortality, it is suggested that children with cellular and mixed CMN are closely followed‐up clinically and radiologically for a minimum of 12 months after primary surgery 18 …”
Section: Discussionmentioning
confidence: 99%
“…As suggested by the aggressive pathological features, the cellular variant is more aggressive with local recurrence, and distant metastases 17 . Since recurrence and metastasis in cellular CMN are much more common and carry a high mortality, it is suggested that children with cellular and mixed CMN are closely followed‐up clinically and radiologically for a minimum of 12 months after primary surgery 18 …”
Section: Discussionmentioning
confidence: 99%
“…Referencias bibliográficas local, invasión al retro peritoneo y metástasis pulmonares y cerebrales en la variante celular 20,21 . En la histología, el NMC presenta haces entrelazados de células fusiformes con aspecto fasciculado, rodeando a túbulos y glomérulos [17][18] como en nuestro caso.…”
Section: Discussionunclassified
“…El NMC se considera benigno y con pronóstico favorable luego de la nefrectomía radical temprana abierta o laparoscópica y con amplios márgenes de seguridad 19 . Hay casos dependiendo de la variedad histológica y del estadio, con tendencia a la recidiva o con metástasis ganglionares, pulmonares o cerebrales que pueden eventualmente responder a la quimioterapia 20,21 .…”
Section: Congenital Mesoblastic Nephroma: Case Reportunclassified
“…Recurrences are rare and have been described in approximately 4% of the cases . Relapses more commonly occur locally, but distant metastasis in the lung and liver have been reported; bone metastases are extremely rare and account for 5.5% of reported cases with metastasis …”
Section: Discussionmentioning
confidence: 99%
“…12 Relapses more commonly occur locally, but distant metastasis in the lung and liver have been reported; bone metastases are extremely rare and account for 5.5% of reported cases with metastasis. 9,13,14 Subsets of patients who are at high-risk for recurrence include those who are older than 3 months of age at diagnosis, those with a cellular type that contains an NTRK gene-fusion, and those with an incomplete surgical resection of the mass. 9,12,13 Gooskens et al estimated that recurrence with cellular CMN was as high as 10% with a mortality of 57% in the cohort reviewed.…”
Section: Discussionmentioning
confidence: 99%